2021
DOI: 10.2147/rmhp.s299963
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status is Independently Associated with Insulin Resistance in Patients with Type 2 Diabetes Mellitus

Abstract: Purpose This study aimed to examine whether 25-hydroxyvitamin D (25OHD) levels (an indicator of vitamin D status) are independently associated with insulin resistance (IR) in patients with type 2 diabetes mellitus (T2DM). Patients and Methods This was a cross-sectional study. Participants with T2DM were recruited from the Department of Endocrinology in Hebei General Hospital according to inclusion and exclusion criteria. Data on basic characteristics and blood parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Several studies in Caucasian and Asian populations have documented an association between low serum vitamin D levels and pancreatic beta-cell dysfunction and insulin resistance [9][10][11][12]39]. On the contrary, we did not observe any association between vitamin D deficiency and insufficiency and markers of pancreatic beta-cell dysfunction and insulin resistance in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Several studies in Caucasian and Asian populations have documented an association between low serum vitamin D levels and pancreatic beta-cell dysfunction and insulin resistance [9][10][11][12]39]. On the contrary, we did not observe any association between vitamin D deficiency and insufficiency and markers of pancreatic beta-cell dysfunction and insulin resistance in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…The median (IQR) age, BMI, HbA1c, and vitamin D concentration of the participants was 48 years (39-58), 27 kg/m 2 (23-31), 11% (8)(9)(10)(11)(12)(13) or 96 mmol/mol (67-115), and 24 ng/ml (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), respectively. About 54% of the participants were females.…”
Section: Baseline Characteristics Of All Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 , 25 Previous studies have confirmed that vitamin D is independently related to IR in patients with T2DM, but the study applied HOME-IR to reflect insulin resistance. 6 , 26 This article uses a new indicator, the TyG index, to reflect insulin resistance, which may be helpful for future clinical applications. The TyG index is calculated from blood sugar and triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“… 4 From another perspective, vitamin D is associated with glucose homeostasis in type 2 diabetes mellitus (T2DM) patients, and vitamin D levels were negatively related to diabetic complications. 5 Studies further approved that vitamin D is independently associated with insulin resistance (IR) in patients with T2DM, 6 , 7 which may imply that vitamin D is related to the triglyceride-glucose (TyG) index in patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%